2023
DOI: 10.3390/foods12051054
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Traits of Grains and Groats of Barley, Oat and Spelt Grown at Organic and Conventional Fields

Abstract: Barley, oats, or spelt consumed as minimally processed whole grains provide several health benefits, especially when grown under organic field management conditions. Therefore, the effects of organic and conventional farming on the compositional traits (protein, fibre, fat, and ash) of barley, oat, and spelt grains and groats were compared using three winter barley varieties (‘Anemone’, ‘BC Favorit’, and ‘Sandra’), two spring oat varieties (‘Max’ and ‘Noni’), and three spelt varieties (‘Ebners Rotkorn’, ‘Mursk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, genotype directly affects the quality properties of grains such as 1,000 kernel weight (Yalçin et al, 2007). Similarly to Sinkovič et al (2023) we found that β-glucan content is higher in barley grains compared to wheat and genotype has an impact on grain β-glucan content. This result shows that barley could have a greater role in human food as it can improve its physiological effect and provide health benefits (Izydorczyk and Dexter, 2008).…”
Section: Figuresupporting
confidence: 69%
“…In addition, genotype directly affects the quality properties of grains such as 1,000 kernel weight (Yalçin et al, 2007). Similarly to Sinkovič et al (2023) we found that β-glucan content is higher in barley grains compared to wheat and genotype has an impact on grain β-glucan content. This result shows that barley could have a greater role in human food as it can improve its physiological effect and provide health benefits (Izydorczyk and Dexter, 2008).…”
Section: Figuresupporting
confidence: 69%
“…The outer grain coat consists of bran layers (pericarp, coat seed, and aleurone), which mainly represent the insoluble dietary fiber fraction of the grain [ 67 ]. Explaining the correlation between fat and fiber is complicated by the fact that both the fat and fiber contents of the grain are both altered by the dehulling process, in which part of the bran layer is removed along with the hull [ 68 ]. Consequently, the fat and fiber values for dehulled groats reported in Table 2 represent the composition after processing, rather than as harvested.…”
Section: Resultsmentioning
confidence: 99%
“…Spelt grain has ideal combination of protein, carbohydrates, fats, minerals, vitamins, and fiber (Sinkovič et al, 2023). Compared to common wheat, it may have a higher content of protein and fiber, as well certain oligo-minerals and micro elements (e.g.…”
Section: Introductionmentioning
confidence: 99%